Comparative study on functional outcome, complication and readmission rate in bilateral simultaneous versus staggered versus staged total knee replacement: a retrospective study - Pushkarna, Vishal Ashokraj; Reddy, A. V. Gurava (International Journal of Research in Orthopaedics, 2020)
Background: An important source of debate in orthopaedic practices is the choice of performing simultaneously, staggered or staged bilateral total knee arthroplasty (BTKA). Many studies are available which compare bilateral simultaneous vs staged TKA in terms of functional outcome. But still there are no studies which include staggered BTKA (done in a single hospital stay) and compared their functional outcome, associated complication with a 90 days readmission rate. Methods: A retrospective review of 300 TKAs patients who underwent bilateral TKA. Patients were divided into three groups with 100 patients each in simultaneous, staggered, staged group. We use hospital electronic health records database to compare the complication and readmission rates in all three groups. Functional outcome was evaluated pre-operatively using knee society score (KSS), Western Ontario and McMaster Universities Arthritis Index (WOMAC), Oxford knee score, Kujala score and range of motion. Results: The study consists of 234 females and 66 males, among which maximum females were in a simultaneous group while male where more in staggered group. Mean age group in our study was 62.25%. ASA score of 3 was significantly more in staged group. Patient in the staggered group had a better KSS and Kujala score with better range of motion and less readmission and complication rate. Simultaneous BTKA had slightly higher complication rate. Conclusions: This study demonstrates that there is not big significant in functional outcome when comparing simultaneous, staged and staggered bilateral TKA, but still staggered group shows better postoperative functional outcome.